Combinação de percarbonato e persulfato de sódio para remediação por oxidação quimica em solos brasileiros - Nishikawa, Gustavo [UNIFESP] (2021)
The management of contaminated areas and the search for alternatives for the remediation of these areas brought about a constant evolution in techniques. One of the techniques developed is the use of oxidizing chemicals, in processes called In Situ Chemical Oxidation. Different types of oxidants have been applied, such as permanganates, peroxides, and persulfate, among others. The objective of this work was to evaluate the efficiency of sodium percarbonate (PCS) as an oxidizer, considering its impacts on the soil and the potential of its application in combination with sodium persulfate (PS). The chemical properties of three soils: Red Oxisols, Red Yellow Oxisols and Quartzipsamments were evaluated before and after contact with the oxidants PCS and H2O2 at 14 g L-1 and 50 g L-1, to evaluate the effects of oxidants on these soils. Given the characteristics of each oxidant, different effects were observed in the water and soil matrices such as alkaline conditions for the tests with PCS, variations in the concentrations of DO, variations in the concentrations of micro and macronutrients. The evaluation of the interaction of the PCS with the PS in the presence of soil was carried out through batch tests with the variation of the proportions between the oxidants, in which the physical-chemical properties of the solutions were evaluated over time. Another process evaluated was the efficiency of oxidants for anthracene degradation, either alone or in combination, also from batch tests. The results indicated a better efficiency of the PCS in the removal of anthracene mass, compared to the PS and the combined use of these two oxidants. The tests with the combination of these two oxidants showed, in the studies of the physical-chemical parameters, the observation of changes in the values of Eh, pH, OD, where alkaline conditions were probably explained due to the presence of the carbonate ion, OD values higher than those observed in individual processes in relation to the isolated use of PS and lower Eh values also in relation to isolated use compared to PS. Due to these observed physical and chemical changes, it is estimated that the combined use of oxidants can also, based on the characteristics imputed by the PCS (pH, OD and H2O2), promote the activation of the PS, generating a possible improvement of the oxidative process. Thus, the combination of oxidants can have potential use, but it is a complex process, especially when in the presence of soil. Thus, further studies are needed to elucidate the best conditions for remediation.